A Two-Echelon Agricultural Product Supply Chain with Freshness and Greenness Concerns: A Cost-Sharing Contract Perspective. (19th October 2020) - Tan, Manyi; Tu, Manli; Wang, Bin; Zou, Tianyue; Cheng, Hong
Abstract : Agricultural products are basic needs of human beings, and whether they are cultivated in a green (or organic) manner has direct impact on environment and public health. This research incorporates product freshness and greenness into a two-echelon agricultural product supply chain (APSC). Game theoretic analyses are carried out to examine pricing, freshness, and greenness decisions of the supply chain members with and without cost-sharing for greenness investment. Subsequently, we conduct comparative and sensitivity analyses for these optimal decisions and profits of the APSC members under different cases. Numerical experiment is employed to investigate the impact of key parameters on equilibrium decisions and profitability. Analytical and experimental results show that the cost-sharing contract of greenness investment for agricultural products helps to strengthen the supply chain members' effort in improving the greenness and freshness levels of the agricultural product, thereby enhancing both individual and channel profitability of the APSC under certain conditions. This research also reveals a widened profit gap between the producer and the retailer under the cost-sharing contract.